The Way Financial Distress Affects Financial Reporting Delay - Nurquran, Pramesari Dinar; Ardianto, Ardianto (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2023)
Objective: Previous studies identified a significant effect of financial distress experienced by a company on the delay in submitting its audited financial report. However, no analysis to identify whether the effect is direct or indirect by decomposing the total effect calculated. This study conducted further analysis aiming to reveal the mechanism of the way financial distress affects financial reporting delay, whether the effect is entirely direct or there is a portion of indirect effect, by decomposing the total effect using the quality of financial report as a mediating factor. Design/Methods/Approach: Public companies listed at Indonesian Stock Exchange (IDXI), whichever delay in submitting audited financial reports were targeted population, the purposive sampling method was implemented to collect financial reports within the 2014-2020 period. Logistic regression, linear regression, and a technique to decompose the effect into four components under the mediation model are analysis methods. In addition, the quality of the financial report measured by the Beneish Score was used as a mediator variable. Findings: This study found that the more severe the financial distress experienced by a company, the more likely it will delay submitting its audited financial report. Although there is an indication that financial distress affects the quality of the financial report, however no significant evidence that the quality of the financial report mediates some of the effects of financial distress on financial reporting delay. In other words, the effect of financial distress is direct. Originality/Value: This study delivered new insight by including financial reporting quality as a potential mediating variable in the relationship between financial distress and financial reporting delay. The existence of mediating variable allowed us to decompose the total effect of financial distress on the financial reporting delay and identify whether financial distress's effect on financial reporting delay is direct or indirect. The identification of direct and indirect effects will reveal the mechanism of how financial distress effects affect financial reporting delay. The researchers expected to add new insight, where the use of financial reporting quality as a mediating variable was expected to reveal the mechanism of the relationship between financial distress and financial reporting delay. This study evaluates the relationship between financial distress experienced by companies, financial reporting quality, and financial reporting delay. Practical/Policy implication: The findings of this study suggest that investors have to be more careful in investment decision-making on public companies that delay submitting their audited financial reports, and regulators have to strengthen protection for investors.